Molecular characterisation of grouper iridovirus isolates from Peninsular Malaysia - Hazeri, Maryam; Mohd Daud, Hassan; Abba, Yusuf; Omar, Abdul Rahman; Allaudin, Zeenathul Nazariah; Soltani, Mehdi; Hamdan, Ruhil Hayati; Mohamad, Nora Faten Afifah (Veterinary Association Malaysia, 2017)
Grouper Iriovirus (GIV) is one of the most devastating viral diseases of marine and cultured groupers worldwide. In the current study, 5 presumptive Malaysian GIV isolates were characterised through PCR amplification of the major capsid protein (MCP) gene and phylogenetic analysis of the sequences. The sequences from the five GIV isolates showed 100% homology with each other and a close relationship with grouper iridovirus isolate (GIV_Tn_352), which was clustered in group 1 together with King grouper iridovirus isolate (KGIV_Cy_346), Singapore grouper iridovirus (SGIV), and Crimson snapper iridovirus isolate (CSIV). The phylogenetic tree also showed different degree of relatedness with other Ranavirus strains which were obtained from the blast of GIV MCP gene in the NCBI database. This study confirmed the GIV isolates from Malaysia are related to other isolates that were reported previously.